Manajemen Mutu Hotel Dalwa Syariah - Akhmad Fauzi Hamzah (Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2021)
Abstract: This study examines the quality management of the Dalwa Syariah hotel which is still under the auspices of Pondok Darullugah Wadd'awah. This study is important because so far speaking of quality, it seems that Islamic boarding schools are still lacking in implementation. Moreover, not many Islamic boarding schools have hotels. So the quality is still questionable. This assumption is not entirely true, Hotel Dalwa Syariah implements quality management that is sourced from the values of the Dalwa. The quality management practiced at the Dalwa Syariah hotel are: in accordance with sharia principles, sincere in serving customers, prioritizing blessings and continuous improvement. Keywords: Quality Management